Dahliaphyllum, a new arborescent umbellifer from Guerrero - Constance, Lincoln; Breedolve, Dennis E. (Instituto de Ecología, A.C., 1994)
Dahliaphyllum, a new genus of woody “peucedanoid” Umbelliferae/Apiaceae is described from the general area of Cerro Teotepec in the Sierra Madre del Sur of Guerrero. In both habit and foliage, it is reminiscent of Dahlia section Pseudodendron.